Differential effects of aging in the macular retinal layers, neuroretinal rim, and peripapillary retinal nerve fiber layer - Chauhan, Balwantray; Vianna, Jayme R.; Sharpe, Glen P.; Demirel, Shaban; Girkin, Christopher A.; Mardin, Christian Y.; Scheuerle, Alexander F.; Burgoyne, Claude F. (Ophthalmology, 2020)
Purpose - We determined the differential aging effects of the inner 6 layers of the macula in contrast to the minimum neuroretinal rim width (MRW) and peripapillary retinal nerve fiber layer (RNFL) thickness. - Design - Cross-sectional, multicenter study. - Participants - An approximately equal number of white subjects with a normal ocular and visual field examination in each decade group from 20 to 90 years. - Methods - OCT of the macula, optic nerve head, and peripapillary retina. - Main Outcome Measures - Sectoral measurements of the inner 6 layers of the macula; age-related decline of each of these layers; strength of the associations with age of the macular parameters, MRW, and peripapillary RNFL thickness; and association between ganglion cell layer (GCL) thickness and MRW and peripapillary RNFL thickness. - Results - The study sample comprised 1 eye of 246 subjects with a median (range) age of 52.9 (19.8-87.3) years. Of the 6 layers, there was a statistically significant decline with age of only the GCL, inner plexiform layer, and inner nuclear layer thickness with rates of −0.11 μm/year, −0.07 μm/year, and −0.03 μm/year, respectively. These rates corresponded to 2.82%, 2.10%, and 0.78% loss per decade, respectively, and were generally uniform across sectors. The rate of loss of MRW and peripapillary RNFL thickness was −1.22 μm/year and −0.20 μm/year, corresponding to 3.75% and 2.03% loss per decade. However, the association of GCL thickness change with age (R2 = 0.28) was approximately twice that of MRW and RNFL thickness (R2 = 0.14 for each). - Conclusions - In concordance with histopathologic studies showing age-related loss of retinal ganglion cell axons, we showed a significant decline in GCL thickness, as well as MRW and peripapillary RNFL thickness. The stronger relationship between aging and GCL thickness compared with the rim or peripapillary RNFL may indicate that GCL thickness could be better suited to measure progression of structural glaucomatous loss.
Available online 21 September 2019
Gesehen am 23.04.2020